The moderating effect of psychosocial factors in the relation between neighborhood walkability and children's physical activity. Issue 1 (December 2016) - D'Haese, Sara; Gheysen, Freja; De Bourdeaudhuij, Ilse; Deforche, Benedicte; Van Dyck, Delfien; Cardon, Greet
Abstract Background The study aimed to investigate if psychosocial factors moderate the association between objective walkability and different domains of children's physical activity (PA). A second aim of the study was to investigate the direct associations between psychosocial factors and children's PA. Based on previous literature, it was hypothesized that walkability would be more strongly related to PA among children with negative psychosocial profiles. Methods Data were collected between December 2011 and May 2013 as part of the Belgian Environmental Physical Activity Study in children (BEPAS-child). In total, data from 494 children and one of their parents were included in the study. Children wore an accelerometer for 7 consecutive days and together with one of their parents, they completed the Flemish Physical Activity Questionnaire. Parents filled out a questionnaire concerning their child's psychosocial factors toward PA (i.e. parental attitude toward their child's PA, parental social norm toward their child's PA, parental support, friend support, children's self-efficacy, and perceived benefits and barriers toward sports and PA). Neighborhood walkability was calculated using geographical information systems (GIS). Multilevel cross-classified analyses were conducted. Results Of the 42 investigated interactions between neighborhood walkability and psychosocial factors in relation to PA among children, only 7 significant interactions were found of which 3 were only significant among children from low-income neighborhoods. Parental support and self-efficacy were positive correlates of children's PA in high- and low-income neighborhoods independent of the level of walkability, but effect sizes were small. Conclusions The hypothesis that walkability would be more strongly related to PA among children with negative psychosocial profiles could not be confirmed and in general, psychosocial factors and objective walkability did not interact in relation to children's PA. Focusing on parental support and self-efficacy towards PA can possibly cause small effects on children's PA in both high- and low-walkable neighborhoods, as well as in high- and low-income neighborhoods.